INVESTIGATING TEACHER QUESTION TYPES IN AN EFL (ENGLISH AS A FOREIGN LANGUAGE) PRIMARY SCHOOL IN THAILAND - Chindy Claudya BR; Abd. Rahman; Dian Arief Pradana; St. Shabibatul Rohmah (LUNAR, 2023)
Teacher questions have become an important role in the teaching process, especially in English classes. This study investigates the various types of teacher questions used in the classroom during the teaching and learning process. This study held at primary school in Darul Ulom Nibong Baru, 4082, Sateng Nok, Mueng Yala, Thailand. This study aims to find out the types of questions that are often used by teachers in foreign language classes. The questions were identified and classified based on the framework of Richards and Lockhart (1996) as procedural, convergent and divergent. This study used a qualitative method and data was collected through observation for 55.37 minutes from two teaching sessions. This research was conducted by observing (video recording) both teachers and students and interviewing the teacher. The results of this study indicate that questions with Convergent type is the most frequently used by teachers in class (86%) compared to procedural (9%) and divergent (5%) questions. Convergent question types are often used by teachers because these questions encourage students to always answer based on the material taught by the teacher during the learning process.